2019
DOI: 10.7717/peerj.6923
|View full text |Cite
|
Sign up to set email alerts
|

Use of aerial thermography to reduce mortality of roe deer fawns before harvest

Abstract: In agricultural landscape, there are thousands of young wild animals killed every year. Their deaths are caused mostly by agricultural fieldworks during spring harvest. Among the affected animals there are also fawns of roe deer (Capreolus capreolus), which react to danger by pressing themselves against the ground in order to be protected from predators. There were various methods tested in the past aimed at decreasing roe deer mortality caused by agriculture machinery with varied levels of success. This contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Thermal cameras can be used together with high-resolution RGB cameras [ 28 , 62 , 63 ] to complement the lower spatial resolution of a thermal detector, e.g., 640 × 512 pixels [ 44 , 50 , 64 ]. Although small-scale surface features are omitted in thermal images due to the larger pixel size, the thermal contrast between wild animals and the background land covers enables identifying individuals or aggregations [ 72 ].…”
Section: Rpas-based Thermography In Wild Animal Monitoringmentioning
confidence: 99%
“…Thermal cameras can be used together with high-resolution RGB cameras [ 28 , 62 , 63 ] to complement the lower spatial resolution of a thermal detector, e.g., 640 × 512 pixels [ 44 , 50 , 64 ]. Although small-scale surface features are omitted in thermal images due to the larger pixel size, the thermal contrast between wild animals and the background land covers enables identifying individuals or aggregations [ 72 ].…”
Section: Rpas-based Thermography In Wild Animal Monitoringmentioning
confidence: 99%
“…If no fawn was detected within a meadow, we considered it an 'absence field'. Although most fawn search methods, for example with UAVs, yield very high detection rates (Cukor et al, 2019), we cannot be sure that all fawns were found.…”
Section: Data Collectionmentioning
confidence: 97%
“…These tasks may be useful to quantify and to localize presence of animals in agricultural landscapes, reducing the unintentional kills, and increasing harvest efficiency (Libràn-Embid et al, 2020). Several studies reported important results in optimizing relationships between farming management and the presence of different species of fauna, such as Circus pygargus (Mulero-Pázmány and Negro, 2011), Capreolus capreolus (Cukor et al, 2019), Vanellus vanellus (Israel and Reinhard, 2017).…”
Section: Agroecosystems and Biodiversity Monitoringmentioning
confidence: 99%